Resisting Hitler : Mildred Harnack and the Red Orchestra - Brysac, Shareen Blair (OUP E-Books., 2000)
An account of an American woman who gave her life in the struggle against the Nazi regime. As members of a key resistance group, Mildred and her husband, Arvid Harnack, assisted in the escape of German Jews and political dissidents, and provided economic and military intelligence to the Allies.